Dissociation of Acquisition and Expression of Fear Conditioned Responses Under Working Memory Load - Straube, Thomas; Trippe, Ralf; Schmidt, Stephanie; Weiss, Thomas; Hecht, Holger; Miltner, Wolfgang H. R. (Emotion, 2011)
Previously, it has been suggested that high working memory load (WML) prevents associative learning and, thus, conditioned responses (CRs) during differential-delay fear conditioning. However, previous studies did not distinguish between the effects of WML on the acquisition versus the expression of the CRs. In the present study, we reinvestigated this issue by manipulating WML during either acquisition or postconditioning and showed that the absence of a differential CR under high WML does not indicate the absence of the acquisition of this CR. Thus, a significant CR was observed during a task-free postconditioning phase, and there was no CR during the preceding acquisition phase with high WML. Conversely, a normally acquired CR was impaired by high WML during the postconditioning phase. The results suggest that high WML affects the expression of the CR. If they are not experimentally separated, the effects of WML on the acquisition and expression of the CR may occur together, and the findings may be erroneously interpreted as indicating a lack of associative learning. © 2011 American Psychological Association.
Created from Fastlane, Scopus look-up
Keywords: Attention; Fear conditioning; Skin conductance response; Working memory